Effect of Endophytic Bacteria Inoculation and Eco-enzyme on Kayu Kuku (Pericopsis mooniana Thw.) Seedlings Growth - Arum Sekar Wulandari; Yunik Istikorini; Yus Septiawati (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2023)
Improving the physical quality of kayu kuku seedlings can be done by applying endophytic bacteria and ec-enzymes. The aims of this study were to examine (1) the effect of inoculation of endophytic bacteria on the germination of kuku wood seeds, and (2) the effect of inoculation and application of eco-enzymes on the growth of kuku wood seedlings. The endophytic bacteria were isolated from the shoot of Shorea balangeran plant with the codes SBP 1, SBP 2, and SBP 19. Bacterial application was conducted on seeds and seedlings, while eco-enzyme application was only conducted on kayu kuku seedlings. The results of the research at the seed level showed that inoculation of the endophytic bacteria SBP 19 could accelerate the germination rate of kayu kuku seeds. At the seedling level, inoculation of endophytic bacteria SBP 1, SBP 2, SBP 19 and application of eco-enzymes had no significant effect on height, diameter, number of new leaves, total fresh weight and total dry weight of kayu kuku seedlings. The shoot root ratio of kayu kuku seedlings ranged from 2.66-5.04 and the seedlings quality index ranged from 0.41-0.93, indicating that the seedlings were ready to be transplanted into the field. In general, inoculation of endophytic bacteria had a significant effect on kayu kuku seed germination, but had not been able to increase the growth of kayu kuku seedlings during the 14 weeks of observation. Keywords: Pericopsis mooniana Thw., seed dormancy, seed germination, seedling quality index, shoot root ratio